ANALISIS PERILAKU SISWA TERHADAP KEBIASAAN JAJAN DI SEKITAR SEKOLAHAN (STUDI KASUS DI MI MIFTAHUL AKHLAQIYAH KECAMATAN NGALIYAN SEMARANG) - Supriyono Asfawi; Siti Ainurahmah (Dian Nuswantoro Semarang, 2012)
Background. To attract the attention of consumers, the food and beverage manufacturers to add a few additional ingredients such as dyes. But not all the additional materials used aresafe for health, such as yellow and rodhamin methanil-B where the two materials containing hazardous substances that are carcinogenic heavy metal that can cause liver dysfunction,skin allergies, cancer, respiratory tract irritation, seizures the throat, nausea, diarrhea, vomiting, kidney damage can even result in coma. Habits of primary school age children andconsumerism tend are not careful when spending money given by the parents. It is therefore necessary to study the behavior of students around the school snack habits.Method. This type of research is eksplanatory research and methods used are interviews with a sample approach to cross as many as 67 students sectional.dengan Miftahul AkhlaqiahMI district. Ngaliyan Semarang.Result.The results showed no relationship between students knowledge in the habit of eating snacks with a p value 0.033. And there is no relationship between the attitudes of students inthe habit of eating snacks with a p value 0.150Conclusion. From now on, children are given the knowledge about the dangerous of unhealthy foods.Keywords: Behavior, snacks, food is dangerous. food additives